Intra-arterial chemoembolization as a component of neoadjuvant treatment of rectal cancer. Literature review - R. E. Kalinin; E. P. Kulikov; N. I. Verkin; S. A. Mertsalov; E. Yu. Golovkin; I. N. Shanaev; O .V. Zotova (Сибирский научный медицинский журнал, 2024)
Interventional oncology is a rapidly evolving field of cancer treatment. Minimally invasive techniques, such as transarterial embolization with chemotherapeutic and radioactive agents, are common treatments and are found in many guidelines for the treatment of primary and metastatic liver lesions. It is known that the growth and development of a malignant neoplasm is primarily determined by angiogenesis. Rapid growth is ensured where the formation is directly related to the arterial bed. Therefore, when the drug is injected into the target vessel and providing tissue ischemia, it is possible to achieve a high degree of tumor pathomorphosis. This technique has an advantage for patients who, in some cases, cannot be treated surgically, and also increases the effectiveness of the chemotherapeutic effect. With the advent of necessary equipment in hospitals and the accumulation of experience in the use of minimally invasive interventions, it became possible to implement a new method of treating tumors of various localizations. In this review, we consider the results of domestic and foreign authors on the topic of intra-arterial chemoembolization before surgical treatment in patients with rectal cancer. It is noted that the analysis of the literature revealed a small number of works devoted to the chosen topic, despite the relevance of this problem for modern oncology.